Design analysis of an experimental jet impingement study by using Taguchi method - Celik, Nevin; Turgut, Emre (Springer, 2012)
In current study design analysis of a specified impingement jet application is performed by use of Taguchi method. Some results from a previously done experimental study that includes the impingement of co-axial and single circular jets to the both roughened and smooth heated surfaces are handled. By use of Taguchi method, some results are obtained to show the effect of Reynolds numbers (Re = 20,000 and 40,000), non-dimensional surface to jet exit spacing (H/D = 2, 6, 8 and 10), surface roughness (rough or smooth surface) and jet type (co-axial or circular). Finally, the effects of Reynolds number, surface roughness, jet-to-plate spacing and jet type on impingement heat transfer, by means of average Nusselt number, are found to be respectively, 83, 2, 4.5 and 10.7%.
Keywords: Heat-Transfer Characteristics; Impinging Air-Jet; Nozzle-Geometry; Coaxial Jets; Fluid-Flow; Surface; Parameters; Exchanger; Steel